NATURAL INDICATOR: USE OF RED CABBAGE JUICE AS AN INDICATOR IN FOOD, COSMETIC INDUSTRY AND EDUCATIONAL LABORATORIES - Pardayev , Ulug‘bek Xayrullo o‘g‘li; Xoliqulov , Hamro Jasur o‘g‘li; Tilyabov , Maxsudjon Umurzokovich (Educational Research in Universal Sciences, 2023)
Red cabbage juice has long been known to be a natural indicator. This means that it can be used to determine the pH value of a substance by changing color in response to acidity or alkalinity. In this article, we explore the use of red cabbage juice as an indicator in the food, cosmetic industry, and educational laboratories.